2011
DOI: 10.3109/10520295.2011.608716
|View full text |Cite
|
Sign up to set email alerts
|

Effects of capsaicin on nitric oxide synthase isoforms in prepubertal rat ovary

Abstract: Nitric oxide (NO) has emerged as an important intra-ovarian regulatory factor. We investigated effects of low dose capsaicin (CAP) treatment on the different NOS isoforms in prepubertal rat ovaries. Fifteen 21-day-old female Sprague-Dawley rats were divided randomly into three groups. The first group received no treatment, the second group received 0.5 mg/kg/day CAP dissolved in the vehicle, and the third group was treated with the vehicle only. The animals were euthanized by ether inhalation after 15 days and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
2
1
0
Order By: Relevance
“…Among the study groups in the present study, a significant increase was measured in the number of yellowish follicles in the group 2% compared to the group 6%. Such a high result in follicular development is compatible with the finding reported by Zik et al (2010) that low-dose capsaicin protects ovarian follicles from apoptosis and stimulates follicular development. Likewise, the study by Güler and Zik (2018), which examined the proliferative and apoptotic effects of different doses of capsaicin on granulosa cells in the avian ovary, also reported that low-dose capsaicin treatment had positive effects on avian folliculogenesis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Among the study groups in the present study, a significant increase was measured in the number of yellowish follicles in the group 2% compared to the group 6%. Such a high result in follicular development is compatible with the finding reported by Zik et al (2010) that low-dose capsaicin protects ovarian follicles from apoptosis and stimulates follicular development. Likewise, the study by Güler and Zik (2018), which examined the proliferative and apoptotic effects of different doses of capsaicin on granulosa cells in the avian ovary, also reported that low-dose capsaicin treatment had positive effects on avian folliculogenesis.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, it was thought that the reason for the increase in the number of quail follicles induced by hot pepper seeds was related to the changes in the number and size of the epithelial layer and theca cells surrounding the follicle in the avian ovary as reported by Ozer et al (2005). The histological reason why this difference was observed was considered to be due to the protective effect of capsaicin on follicles from apoptosis and atresia (Zik et al, 2010;Güler and Zik, 2018). Liu et al (2021b) argued that capsaicin increased follicular growth and maturation in avians by activation of TRPV4 (Transient Receptor Potential Vanilloid) and calcium (Ca ++ ) signaling pathway in the ovary along with improvement in ovarian antioxidant capacity.…”
Section: Discussionsupporting
confidence: 51%
“…Histological analysis was performed using a light microscope with a computerized imaging system (Northern Eclipse 7.0; Empix Imaging, Inc., Mississauga, ON, Canada) by two qualified observers blinded to the study. The degree of staining was evaluated based on the intensity score, as previously described (18), in which a score of 0-3 represented absence of staining, weak, moderate and strong staining, respectively. The proportional score was the percentage of cells that stained positive in different cell groups and was scored as: 0, no positivity; 1, <1-25%; 2, 26-50%; 3, 51-75%; 4, 76-100% positive staining.…”
Section: Animals and Drugsmentioning
confidence: 99%